2021
DOI: 10.1177/2325967120969902
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of the Top Cited Articles in Sports and Exercise Medicine

Abstract: Background: Although citation analysis is common in many areas of medicine, there is a lack of similar research in sports and exercise medicine. Purpose: To identify and examine the characteristics of the 100 top cited articles in the field of sports and exercise medicine in an effort to determine what components make an article highly influential. Study Design: Cross-sectional study. Methods: The Web of Science, Scopus, and PubMed databases were used to determine the 100 top cited articles from 46 journals in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 37 publications
5
17
0
1
Order By: Relevance
“…Comparatively, a bibliometric analysis focused on overhead throwing athletes found that the top-cited article had 471 citations, 111 an analysis on sports and medicine in football found that the top-cited article had 869 citations, 31 and an analysis on the broader field of sports and exercise medicine found that the top-cited article had 7228 citations. 90 As with other citation analyses related to sports medicine, the majority of our top-cited articles were published within the past 2 decades, reflecting rapid growth in research within the field. 31,90,121 In our study, 96 of the top 100 articles were published within the United States.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Comparatively, a bibliometric analysis focused on overhead throwing athletes found that the top-cited article had 471 citations, 111 an analysis on sports and medicine in football found that the top-cited article had 869 citations, 31 and an analysis on the broader field of sports and exercise medicine found that the top-cited article had 7228 citations. 90 As with other citation analyses related to sports medicine, the majority of our top-cited articles were published within the past 2 decades, reflecting rapid growth in research within the field. 31,90,121 In our study, 96 of the top 100 articles were published within the United States.…”
Section: Discussionmentioning
confidence: 90%
“…90 As with other citation analyses related to sports medicine, the majority of our top-cited articles were published within the past 2 decades, reflecting rapid growth in research within the field. 31,90,121 In our study, 96 of the top 100 articles were published within the United States. This is somewhat expected, as collegiate sports are very popular in North America, along with the rapidly growing field of sports medicine.…”
Section: Discussionmentioning
confidence: 90%
“…This type of study could offer readers the general aspects of research topic on distribution by country, institution, author, and journal. Bibliometric methods have been used in many research fields, including stroke (Feng et al, 2013) and exercise (Fares et al, 2017;Khatra et al, 2021). From the perspective of research progress, the number of clinical trials and papers on stroke rehabilitation has increased in the past years (Feng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The article is published with Open Access at https://www.temjournal.com/ still needs to be explored and explored more deeply [1], [2], [3]. Other countries can adopt innovations in sports in the development of sports achievements, one of which is by looking at the latest trend profiles in sports research [4], [5] through the Scopus document. In this case, librarians and researchers have the opportunity to contribute significantly to the advancement of the sports field in their country.…”
Section: Introductionmentioning
confidence: 99%